2018
DOI: 10.1590/s0102-053620180322
|View full text |Cite
|
Sign up to set email alerts
|

Biometric analysis in maize genotypes suitable for baby corn production in organic farming system

Abstract: The aim of this study was to estimate and quantify the degree of association between phytotechnical variables for simultaneous selection of maize genotypes suitable to produce baby corn. Seven genotypes were arranged in field in randomized complete block design with four replicates. Genetic parameters, simple, path and canonical correlations of phytotechnical variables were estimated. The variables production of marketable spikes, length of marketable spikes, final plant stand and plant height showed over 80% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…All evaluated traits acted in accordance with the assumption of normality of error distribution (p = .05) by the Lilliefors test and homogeneity of residual variances (p = .05) by the Bartllet test. These results have proved that, normally, the mathematical assumptions needed to conduct the analysis of variance and further studies were satisfied [23].…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…All evaluated traits acted in accordance with the assumption of normality of error distribution (p = .05) by the Lilliefors test and homogeneity of residual variances (p = .05) by the Bartllet test. These results have proved that, normally, the mathematical assumptions needed to conduct the analysis of variance and further studies were satisfied [23].…”
Section: Resultsmentioning
confidence: 75%
“…The low correlation observed between the insertion height of the first cob and the stripped cob diameter with the grain yield was caused by the negative indirect effects via the stripped cob length, number of rows of grains per cob, plant height, and total number of cobs, with very low values similar to the ones reported by [23]. Conversely, when a direct effect displays positive results, indirect effects are responsible for the lack of correlation [38].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Alves et al (2016) found a positive phenotypic correlation between phenological and nutritional characters (protein and energy) in corn genotypes. For Nascimento et al (2018), significant correlations between bromatological and agronomic variables show that, the higher the final state of the plant and the greater production of marketable ears, the greater dry mass and the higher crude protein content can be verified, the results show that, by indirect selection, based on the final state of the plant and the production of marketable tips, the authors can select corn genotypes for forage production. High and positive loads of the ear diameter (ED) in the I canonical pair, number of rows per ear (NRG) in the II canonical pair, and negative in the ear length (EL), justified the increase in the levels of total bioactive carotenoids (CAR) for all canonical pairs (Figure 3).…”
Section: Resultsmentioning
confidence: 91%
“…The morpho-agronomic characters showed a positive and high-magnitude correlation with most bromatological characteristics, such a result showed that the morpho-agronomic traits influenced bromatological features, since they increased simultaneously (Crevelari et al, 2019). Using only path analysis and canonical correlations allow a clearer interpretation of the association between two or groups of variables and the interference that others have in this association (Nascimento et al, 2018). It is important to note that the correlations in corn can be altered by the environmental conditions exposed to the genotypes.…”
Section: Figurementioning
confidence: 94%